World languages for Black Linguistic Reparations - Austin, Tasha; Anya, Uju (Foreign language annals, 2024)
This conceptual work highlights the history of Black erasure throughout the existence of world languages (WLs) as a field of study in the United States. It outlines the unique challenges faced by African descended learners who have and continue to pursue WL study in US classrooms. These include but are not limited to reduced local funding and programmatic expectations due to the remnants of anti‐Black educational policies, monolingual and imperial language ideologies prevalent in texts and pedagogical approaches, and generations of segregation in and outside of schools. Finally, this work proposes WLs serve as a site of Black Linguistic Reparations through, (1) the redistribution of resources in the field, (2) the repair of enacted WL teaching to meet the calls of ACTFL's standards for preparing students for communication in a pluralistic society, and (3) a recreation of the “world” as narrated through a global, rather than a white Western lens. The Challenge The decline in World Language (WL) educators reflects long standing barriers to WL study rooted in the anti‐Black underpinnings that shaped the field. How has the development of the US WL study systematically excluded Black communities? How might acknowledging and repairing those harms systemically and programmatically reinvigorate our field?